2007
DOI: 10.1097/01.ccm.0000275266.33910.8d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of levosimendan on acute pulmonary embolism-induced right ventricular failure*

Abstract: A gradual increase in pulmonary artery pressure induced by pulmonary embolism persistently worsens pulmonary artery hemodynamics, right ventricular contractility, right ventricular-pulmonary arterial coupling, and cardiac output. Levosimendan restores right ventricular-pulmonary arterial coupling better than placebo, because of combined pulmonary vasodilation and increased right ventricular contractility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(50 citation statements)
references
References 40 publications
6
38
1
5
Order By: Relevance
“…In a few previous animal studies, levosimendan acutely improved the function of a failing RV directly or through afterload reduction. [10][11][12][13][14] Data on levosimendan in patients with PAH are very sparse and conflicting. [15][16][17][18] The aim of this study was to investigate the effects of levosimendan in a rat pulmonary trunk banding (PTB) model of RV hypertrophy and failure and in a monocrotaline (MCT) rat model of PAH.…”
Section: Introductionmentioning
confidence: 99%
“…In a few previous animal studies, levosimendan acutely improved the function of a failing RV directly or through afterload reduction. [10][11][12][13][14] Data on levosimendan in patients with PAH are very sparse and conflicting. [15][16][17][18] The aim of this study was to investigate the effects of levosimendan in a rat pulmonary trunk banding (PTB) model of RV hypertrophy and failure and in a monocrotaline (MCT) rat model of PAH.…”
Section: Introductionmentioning
confidence: 99%
“…The predominant distal vasodilator effect (RPA) of levosimendan with mild vasodilatory effect on CPA in the vessels from the PE animals could preserve the ventricular-arterial coupling and the proximal-distal PA coupling during the treatment of PE-induced PH through avoiding the increase of proximal arterial stiffness [7,22]. We have previously shown that proximal PA vasoconstriction induced by vascular smooth muscle activation improves both buffering and conduit function of the PA during acute PH mainly due to the increase in wall viscosity, preventing increased wall stiffness secondary to the recruitment of collagen fibers [23].…”
Section: Discussionmentioning
confidence: 99%
“…There are several animals studies in different acute pulmonary hypertension (PH) models secondary to thromboxane A2 infusion [5], endotoxemia [6], acute pulmonary embolism (PE) [7,8], and hypoxia [9] and some clinical studies that demonstrated the vasodilator effect of levosimendan on the pulmonary circulation, restoring right ventricular-arterial coupling as it increased right ventricular contractility concomitantly [10,11]. Acute PE-induced PH results from two main mechanisms: the mechanical obstruction of pulmonary vessels (passive mechanism) and the arterial vasoconstriction secondary to pulmonary neurohumoral activation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…По ре зультатам небольших клинических исследований у больных с ТЭЛА при ингаляции оксида азота мо жет улучшиться гемодинамика и газообмен [266,267]. Предварительно показано, что при использова нии левосимендана может восстановиться баланс между ЛА и ПЖ при острой ТЭЛА за счет сочетания вазодилатации легочных сосудов и повышения со кратимости ПЖ [268].…”
Section: пульмонология 2015; 25 (6): 649-684unclassified